Campylobacter concisus - Biljana Miljković-Selimović; Tatjana Babić; Branislava Kocić; Ema Aleksić; Adam Malešević; Zoran Tambur (Journal of Infection in Developing Countries)
Campylobacter concisus has been described as the etiological agent of periodontal disease, inflammatory bowel diseases, and enterocolitis. It is also detected in healthy individuals. There are differences between strains in healthy individuals and affected ones by production of two exototoxins. In this mini review authors discuss major facts about cultivation, isolation, virulence and immune response to C. concisus.